Engineered living bioassemblies for biomedical and functional material applications - Guimarães, C. F. (2022)
Recent breakthroughs in biofabrication of bioasemblies, consisting of the engineered structures composed of biological or biosynthetic components into a single construct, have found a wide range of practical applications in medicine and engineering. This review presents an overview of how the bottom-up assembly of living entities could drive advances in medicine, by developing tunable biological models and more precise methods for quantifying biological events. Moreover, we delve into advances beyond biomedical applications, where bioassemblies can be manipulated as functional robots and construction materials. Finally, we address the potential challenges and opportunities in the field of engineering living bioassemblies, toward building new design principles for the next generation of bioengineering applications.Â